PREFERENCE F OR PURPOSE BUILT RETIREMENT NEIGHBOURHOOD AMONG THE CHINESE ELDERLY IN SMALL TOWNS IN MALAYSIA - Hassan, Norhaslina; Jiaqi, Tan (PLANNING MALAYSIA, 2017)
The popularity of retirement villages in many developed countries provides a potential market in Malaysia, which is rapidly facing an ageing society. However, little is known about the purpose-built retirement neighbourhood especially its desirability among the local elderly and niche in smaller towns which are poised to reap economic benefits from their locational advantage trending the retirement industry in the region. This study aims to firstly, explore the desirability of retirement neighbourhood among the Chinese elderly in Segamat using semistructured interviews and secondly, identify the niche market of such neighbourhood and its potential contribution to support development strategy of the town. The preference for retirement neighbourhood as an alternative living arrangement among the Chinese elderly in Segamat indicates its good potential as a new source of economic growth but requires that public planning facilitates efficient land development process and increase amenity and services for all especially the elderly.